Effects of caffeine intake and performance pressure on working memory - Lestari, Laila Indra; Kusrohmaniah, Sri (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
Performance pressure and caffeine consumption, a common combination in daily life, have both been shown to affect cognitive performance. However, previous research has not fully elucidated the extent to which the effects of caffeine and performance pressure impact cognitive function, especially working memory. This study aims to examine the possibility that caffeine can enhance working memory performance under pressure. A total of 61 participants aged 18 to 32 participated, divided into four groups. Experiment-based data collection was conducted with a single-blind design. Working memory was measured by Modular Arithmetic Tasks with the OpenSesame program. All participants were asked to perform arithmetic tasks and arousal levels were measured using the Galvanic Skin Response (GSR). The findings revealed no evidence of an interaction effect of caffeine intake and performance pressure on working memory (F= .632, p= .431,hp2= .012). Given the prevalence of caffeine intake prior to facing high-pressure situations, the consumption of a cup of coffee does not improve cognitive performance as many would expect. However, caffeine intake had a stabilizing effect on the skin conductance response values during performance under pressure. Clinical psychologists can use a daily dose of caffeine as an alternative intervention or preventative measure to help patients reduce performance pressure-related anxiety.